2018
DOI: 10.21037/jgo.2018.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of the efficacy and the toxicity of standard and modified FOLFIRINOX regimens in patients with metastatic pancreatic adenocarcinoma

Abstract: Modified FOLFIRINOX presents the same activity against MPA as standard FOLFIRINOX. We found no significant differences in toxicity, possibly due to patient selection and a higher dose reduction rate in the standard FOLFIRINOX arm. NLR stood as an important prognostic marker and further research is needed to comprehend its biological meaning in pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Instead, the patient-tailored FOLFIRI-NOX regimen used here confirmed its satisfactory tolerance we previously reported in advanced pancreatic adenocarcinoma [13], with no new safety issues observed in comparison with existing literature [17,18,30]. We speculate that the patient-tailored approach we adopted here, which recapitulates similar ones with FOLFIRINOX in pancreatic adenocarcinoma [13,31,32] displayed favorable tolerance profile thanks to the deal made between the decreased dose intensity of the three cytotoxics and the global duration of treatment, somewhat allegedly avoiding over-or under-exposure to the drugs [33]. Thus, median actual delivered dose intensities were of the order of~70% (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Instead, the patient-tailored FOLFIRI-NOX regimen used here confirmed its satisfactory tolerance we previously reported in advanced pancreatic adenocarcinoma [13], with no new safety issues observed in comparison with existing literature [17,18,30]. We speculate that the patient-tailored approach we adopted here, which recapitulates similar ones with FOLFIRINOX in pancreatic adenocarcinoma [13,31,32] displayed favorable tolerance profile thanks to the deal made between the decreased dose intensity of the three cytotoxics and the global duration of treatment, somewhat allegedly avoiding over-or under-exposure to the drugs [33]. Thus, median actual delivered dose intensities were of the order of~70% (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Schlick et al [26] evaluated 123 metastatic PC (mPC) patients who underwent FOLFIRINOX treatment, showing by multivariate analysis that BMI > 25 and CEA > 4 at the time of onset of advanced disease could be interpreted as independent negative prognostic factors for OS and for toxicity, also suggesting a role for clinical parameters in patient selection. Other parameters such as the neutrophil-to-lymphocyte ratio (NLR), a marker of systemic inflammation, could be considered for selection, but further clinical studies are needed to support this [27], especially in an adjuvant setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, different from these promising results, de Jesus et al have not found significant discrepancy in toxicity between patients with metastatic pancreatic adenocarcinoma treated with standard and modified FOLFIRINOX regimens, possibly due to patient selection and a higher dose reduction rate in the standard FOLFIRINOX arm. Moreover, the activities against metastatic pancreatic adenocarcinoma of the two regimens are similar in a retrospective study [41]. Therefore, the effective modification agent is still under exploration.…”
Section: Corresponding Measures To Override Limitations For Chemotherapymentioning
confidence: 99%
“…To decrease the accompanied toxicity and adverse effect of two prominent regimens, FOLFIRINOX and the doublet of gemcitabine and nab-paclitaxel, the modifications of the FOLFIRINOX regimen to decrease the toxicity profile and keep a similar anti-tumour effect as the standard one at the same time have been tested [9,41]. Mahaseth et al reported that modified FOLFIRINOX (discontinuation of the bolus 5-FU and administration of growth factors) has an improved safety profile, especially with respect to neutropenia, fatigue, and vomiting, with maintained efficacy in metastatic PDAC [42].…”
Section: Corresponding Measures To Override Limitations For Chemotherapymentioning
confidence: 99%